Law of two child norm in panchayats - "Buch, Nirmala" (New Delhi, 2006)
This book seeks to examine the Law of two-child norm for contesting Panchayat elections and to continue after being elected in the total Context of Rural Women in the traditional patriarchal society. It explores the consequences of its implementation in five states -Andhra Pradesh, haryana, Madhya Pradesh, Orissa and Rajasthan. Further assessing the efficacy of the two-child norm to influence reproductive choices, it also analyses its negative implications on the status of women, the precarious Child Sex Ratio and women's participation in governance. The book will be of great interest and use for Policy makers, researchers and development workers. About The Author: Mrs Nirmala Buch , a former officer of Indian administrative service, has been Secretary to the Government of India in the Ministry of Rural development, Chief Secretary of Madhya Pradesh and Vice Chairperson of the national Environmental Appellate Authority.
Keywords: Panchayat-India